2019
DOI: 10.4081/or.2019.8136
|View full text |Cite
|
Sign up to set email alerts
|

Rotator interval closure: inconsistent techniques and its association with anterior instability. A literature review

Abstract: The Rotator interval (RI) is an anatomic space in the anterosuperior part of the glenohumeral joint. An incompetent or lax RI has been implicated in various conditions of shoulder instability and therefore RI has been frequently touted as an area that is important in preserving stability of the shoulder. Biomechanical studies have shown that repair of RI ligamentous and capsular structures decreases glenohumeral joint laxity in various directions. Clinical studies have reported successful outcomes after repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Numerous clinical studies with rotator interval closure as adjunctive procedures have reported successful outcomes and suggested that indications for rotator interval closure be considered when the following conditions arise clinically: (1) anterior instability with a positive sulcus finding that persists in external rotation; (2) symptomatic instability and laxity in the inferior direction that does not disappear in external rotation with the arm at the side; (3) significant laxity and a large sulcus in the setting of multidirectional instability; and (4) patients with posterior instability that have an incompetent rotator interval [52,53]. In our study, capsular plication or rotator interval closure was performed as an adjunctive stability procedure in 130 (38.3%) shoulders in 10 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies with rotator interval closure as adjunctive procedures have reported successful outcomes and suggested that indications for rotator interval closure be considered when the following conditions arise clinically: (1) anterior instability with a positive sulcus finding that persists in external rotation; (2) symptomatic instability and laxity in the inferior direction that does not disappear in external rotation with the arm at the side; (3) significant laxity and a large sulcus in the setting of multidirectional instability; and (4) patients with posterior instability that have an incompetent rotator interval [52,53]. In our study, capsular plication or rotator interval closure was performed as an adjunctive stability procedure in 130 (38.3%) shoulders in 10 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible reason for the good outcomes may be the selective augmentation procedures, namely RIC and HSR. As several systematic review articles 10,11,18 have reported that the effectiveness of RIC was not conclusive, owing to inconsistent RIC procedures, RIC is unpopular despite its lower technical difficulty and invasiveness as compared with HSR. However, it has been reported that RIC is possibly an effective augmentation procedure for traumatic shoulder instability in collision/contact athletes.…”
Section: Discussionmentioning
confidence: 99%
“…8 RIC is less popular than HSR because of inconsistencies in surgical procedures and results from biomechanical studies. 10,11,18 We have been subjecting the subscapularis tendon to RIC with the arm in maximum external rotation at side, and we believe that it is a reliable procedure of low complexity and invasiveness. 31 Since 2012, we have been performing ABR or ABBR in combination with RIC and/or HSR as selective augmentations depending on the risks of recurrence, such as younger age, larger glenoid bone loss, or competitive contact/collision athletes.…”
mentioning
confidence: 99%
“…The RI and its contribution to glenohumeral rotation, stability, and shoulder kinematics are yet to be completely understood. 6,7 Therefore, minimally invasive techniques, when possible, may help maintain native anatomy and function. In instances when the arthroscope is inserted into the joint through the posterior viewing portal and no additional pathology exists other than the LHB tendon, it is possible to perform a diagnostic arthroscopy with LHB tenotomy without establishment of an anterior portal by using a standard 18-gauge spinal needle (Becton Dickinson, Franklin Lakes, NJ) and performing the saber technique.…”
mentioning
confidence: 99%